The cassava genome: current progress, future directions - Prochnik, S.E.; Marri, P.R.; Desany, B; Rabinowitch, P.D.; Kodira, C; Fauquet, Claude M.; Tohme, Joseph M.; Rodríguez, F.; Mohiuddin, M; Harkins, T; Rokhsar, DS; Rounsley, S. (Springer, 2012)
The starchy swollen roots of cassava provide an essential food source for nearly a billion people, as well as possibilities for bioenergy, yet improvements to nutritional content and resistance to threatening diseases are currently impeded. A 454-based whole genome shotgun sequence has been assembled, which covers 69% of the predicted genome size and 96% of protein-coding gene space, with genome finishing underway. The predicted 30,666 genes and 3,485 alternate splice forms are supported by 1.4 M expressed sequence tags (ESTs). Maps based on simple sequence repeat (SSR)-, and EST-derived single nucleotide polymorphisms (SNPs) already exist. Thanks to the genome sequence, a high-density linkage map is currently being developed from a cross between two diverse cassava cultivars: one susceptible to cassava brown streak disease; the other resistant. An efficient genotyping-by-sequencing (GBS) approach is being developed to catalog SNPs both within the mapping population and among diverse African farmer-preferred varieties of cassava. These resources will accelerate marker-assisted breeding programs, allowing improvements in disease-resistance and nutrition, and will help us understand the genetic basis for disease resistance.